IMPLEMENTASI PROGRAM DONOR DARAH BERBASIS KOMUNITAS SEBAGAI BENTUK PENGABDIAN KEPADA MASYARAKAT JASERCO PEDULI DI KOTA SERANG - Hafidz Hanafiah; Muhammad Erry Budi Sentosa; Mohamad Muhibbudin; Pratama Jaya; Budi Susanto; Whidy Lisarsa; Alamsyah Alamsyah; Joni Prihatin (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2026)
The availability of safe and sustainable blood stocks is a crucial health challenge, particularly in Serang City. The low public awareness to donate blood regularly is often the main cause of fluctuation and shortage of blood stocks at the Blood Transfusion Unit (UTD) of the Indonesian Red Cross (PMI). This community service aims to implement a community-based blood donation program initiated by the “Jaserco Peduli” group as a concrete effort to increase blood stock availability and build a culture of health concern in the Serang City community. The implementation method of this activity uses a participatory approach, which includes stages of socialization and education regarding the importance of blood donation, intensive coordination with the UTD of PMI Serang City, and the direct execution of blood donation actions involving community members and the general public. The results of this community service activity showed a significant increase in public enthusiasm. The program successfully gathered 25 donors, with 25 bags of blood deemed suitable for use and distributed to the UTD of PMI Serang City. In addition, there was an increase in participants' understanding of the requirements, procedures, and benefits of donating blood based on post-activity evaluation. It can be concluded that the implementation of the community-based blood donation program by Jaserco Peduli is an effective, collaborative, and sustainable service model. The synergy between the community, health institutions, and the public has proven to be an alternative solution in maintaining blood supply stability and improving public health awareness in Serang City.